2023
DOI: 10.2147/ijgm.s407532
|View full text |Cite
|
Sign up to set email alerts
|

Post-Acute Care for Traumatic Brain Injury Patients in Taiwan

Abstract: Background Traumatic brain injury (TBI) can result in functional impairments. Many patients with TBI require post-acute care to improve their functional skills and allow for greater self-independence and a better quality of life. Taiwan’s National Health Insurance proposed a nationwide post-acute care program in 2017 for patients with traumatic brain injury. The program’s goal was to maximize patients’ functional recovery and make it possible for them to return to their homes and communities. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…The PAC program can be a transition period between admission and home care. Our hospital has different PAC programs such as stroke PAC [ 27 ], traumatic brain injury PAC [ 28 ], heart failure PAC [ 29 ], burn injury PAC [ 30 ], and/or fragility fracture PAC. A 5-year study has shown that patients who received the integrated Hip Fracture Care Pathway program can have better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The PAC program can be a transition period between admission and home care. Our hospital has different PAC programs such as stroke PAC [ 27 ], traumatic brain injury PAC [ 28 ], heart failure PAC [ 29 ], burn injury PAC [ 30 ], and/or fragility fracture PAC. A 5-year study has shown that patients who received the integrated Hip Fracture Care Pathway program can have better outcomes.…”
Section: Discussionmentioning
confidence: 99%